Anthocyanins and flavonoid glycosides as bioactive of Prosopis nigra mesocarp flour - Perez, Maria Jorgelina (2014)
The purple colour of Prosopis pods and the different colour that showed the pods flour from different collections of Prosopis nigra draw our attention. The colour of foods and beverages is one of most important properties to obtain their acceptability. The aim of this study was to determine the content of phenolic compounds and pigments responsible of the pods colours and the biological properties. The colour of the algarrobo pods is related to the content of anthocyanins. P. nigra pods having higher content of anthocyanins are darker (purple).The P. nigra flour shows a pattern characterized by the occurrence of anthocyanins (principally cyanidin-3-glucoside) as well as 14 flavonoid glycosides. The main compounds were quercetin O-glycosides and apigenin- C-glycosides. Furthermore, the polyphenolic ethanolic extracts of P. nigra as well as anthocyanins enriched aqueous extracts from P. nigra showed free radical scavenging activity. Considering the easy extraction of pigments from P. nigra flour and its stability in aqueous system during storage as well as its biological properties, the extract enriched in anthocyanins could be added in food systems. Furthermore, the flour obtained from P. nigra mesocarp showed activity against cyclooxigenase, a pro-inflammatory enzyme.. The results suggest that the P. nigra mesocarp flour could be considered as functional food. .Acknowledgements We thank MINCYT (CH/11/13) ?Valorizacion de frutos nativos sudamericanos. Metabolomica de frutos de algarrobos?, and ANPCyT (PICT 1959) for financial support.